Biomechanical optimization of bone plates used in rigid fixation of mandibular symphysis fractures. - Lovald S; Baack B; Gaball C; Olson G; Hoard A (Journal of Oral & Maxillofacial Surgery (02782391), 2010)
PURPOSE: To design and optimize a bone plate for fractures of the mandibular symphysis that will provide maximum fracture stability with minimal implanted volume and patient intrusion. The design will be driven by the unique biomechanics specific to this fracture location. MATERIALS AND METHODS: A finite element model of a fractured human mandible was created using computed tomography scans. The boundary conditions included simulating molar, canine, and incisal loading. The bone plate design process included a shape optimization routine and design parameter analysis using the model. The optimized bone plate design was finally compared with standard bone plate configurations according to stress and strain measures. RESULTS: Compared with the miniplate combination, the InterFlex III plate, with the same thickness and just 14% more implanted volume, had only 55% of the plate stress and 25% less fracture strain under the strongest loads considered by the model. Compared with the band/fracture plate combination, the InterFlex plate had 88% of the fracture strain and 74% of the plate stress, despite having only 60% of the plate volume. CONCLUSIONS: The results have demonstrated that the new optimized plate is a hybrid of fixation hardware with the small profile of the smallest miniplate configuration and the superior fixation strength and safety that exceeds that of the larger fracture plate configuration.